2013
DOI: 10.1071/wf12178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire on cation content in water: a laboratory simulation study

Abstract: Laboratory experiments were carried out to explore the effect of thermal shocks (as occur during fire) and simulated rainfall events on cation leaching dynamics in an organic rich Leptic Umbrisol soil. The soil samples were collected in the field using specially designed lysimeter boxes that allow sampling and application of thermal shock treatments and simulated rainfall while keeping the soil structure unaltered. The soil temperature during the thermal shocks and degree-hours of accumulated heat were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…The lower concentration of exchangeable potassium in burned soils under natural rainfall conditions compared to unburned ones does not coincide with previous studies (Caon, Vallejo, Ritsema, & Geissen, ; Certini, ), which reported an ephemeral increase in potassium after fire. Such contrasting results may be due to the fact that, as our first soil sampling was carried out 8 months after fire, leaching or surface runoff may have occurred in the period between fire and sampling (Cancelo‐González, Rial‐Rivas, & Díaz‐Fierros, ).…”
Section: Discussionmentioning
confidence: 98%
“…The lower concentration of exchangeable potassium in burned soils under natural rainfall conditions compared to unburned ones does not coincide with previous studies (Caon, Vallejo, Ritsema, & Geissen, ; Certini, ), which reported an ephemeral increase in potassium after fire. Such contrasting results may be due to the fact that, as our first soil sampling was carried out 8 months after fire, leaching or surface runoff may have occurred in the period between fire and sampling (Cancelo‐González, Rial‐Rivas, & Díaz‐Fierros, ).…”
Section: Discussionmentioning
confidence: 98%
“…Post-fire losses of P by overland flow, however, have been poorly investigated (Cancelo-González et al, 2013;DeBano et al, 1998;Díaz-Fierros et al, 1990;Lasanta and Cerdà, 2005). In Portugal, particularly few studies have measured post-fire P export by overland flow (Coelho et al, 2004;Ferreira et al, 1997Ferreira et al, , 2005Thomas et al, 1999Thomas et al, , 2000aThomas et al, , 2000bWalsh et al, 1992), especially considering the more than 100.000 ha that are burnt each year.…”
Section: Introductionmentioning
confidence: 95%
“…SOC curves followed a very similar trend, and relevant effects at low temperatures were not observed. Neither qualitative nor quantitative changes in SOC have been observed at low temperature ranges between 150°C and 220°C (Fernández et al, 1997;Badía & Martí, 2003). Main changes occur at intermediate temperatures (Certini, 2005).…”
Section: Soil Water Repellency and Soil Organic Carbon Response To Hementioning
confidence: 97%
“…Thus, this older, more recalcitrant GRSP would become measurable (at highest temperatures) with the breakdown of aggregates when the organic matter combustion takes place, which could be the explanation for the increases observed in most cases in the temperature range between 180°C and 200°C (Figure 2). Many authors (Badía & Martí, 2003;García-Corona et al, 2004;Marcos et al, 2007) have described a decrease in AS with temperature in laboratory heating. Zavala et al (2010) did not find a decrease in AS at temperatures below 150°C but did at 250°C in sandy loam and loamy sandy soils.…”
Section: Glomalin-related Soil Protein Response To Heating Treatmentsmentioning
confidence: 99%